Analysis of Students' Understanding of Mathematical Concepts in Solving Comparative Problems - Hafifah Debby Puspithasari; Heni Pujiastuti (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
The purpose of this study is to analyze the students 'concept and students' mistakes while solving the comparison task. This experiment used qualitative descriptive methods. The Subjects of this experiment were the students in Daan Mogot Junior High School grade. Data were collected by observation method. The result shows that the percentage of students' concept understanding while solving the Comparison is 67.18%, the result of object clarification according to another character is 37.69%, giving sample and non-sample is 99.04%, presenting concept by the right form mathematical representation is 90,38%, developing the need-qualification and enough-qualification concept is 14,1%, using the benefit and choosing the certain procedure is 73,46% and applying concept and algorithm to solve the problem is 41.15%. The students' mistakes while solving the Comparison task are: conceptual mistake, calculation mistake, using the wrong logic to conclude, using the wrong theorem, not checking the task. Some indicators such as the students don't understand enough about the abstract question, conceptual proof, how to start the proof, they get difficulties to remember the definition in conceptual proofing and use them to construct the proof, the students are not paying attention while reading the question, and they are having less confidence to answer the questions are the causes of the students' mistake while solving comparison. Keywords: Conceptual Understanding, students' mistake, Comparison